Abnormal uterine bleeding: a study of menstrual patterns and histopathological patterns in perimenopausal females - Jain, Mahima; Gorania, Nilesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: In gynecology out-patient department there is a large group of patients especially in perimenopausal age group who present with various menstrual disorders. These can be as such caused due to various etiologies, which need to be investigated as line of management is thereupon decided. This study is undertaken to know the various abnormal uterine bleeding in perimenopausal women, and their histopathological pattern. Methods: This study is done at PDU medical college hospital, Rajkot, Gujarat which is a tertiary care centre. A retrospective analysis of 268 cases clinically presenting with abnormal uterine bleeding is done. They are further posted for dilatation & curettage after thorough investigation to rule out other pathologies. The endometrial samplings from the D& C material are collected and sent for histopathological assessment. The data is recorded and further analysed. Women between 40-55 years age group are included in this study. Women with diagnosed pelvic pathology, endocrinal cause and bleeding tendencies are excluded from the study. Results: In our study almost all menstrual disorders are found, commonest being menorrhagia in 42.16%. Other patterns reported are metrorrhagia in 3.35%, oligomenorrhea in 14.80%, polymenorrhea and polymenorrhagia in 5.22% and 5.59% cases. Post-menopausal bleeding is found in one case. The histopathological diagnoses reported in this study are proliferative and secretory phase in 26.49% and 19.77% respectively. Other endometrial hyperplasias reported are Swiss cheese in 1.86%, simple cystic hyperplasia in 12.31%, complex hyperplasia with or without atypia in 7% and 4.10% respectively. Malignancy is found in 2 cases. Conclusions: From this study it is well established that endometrial sampling from D&C material still remains the gold standard in diagnosis of various endometrial pathologies in low resource set-up. Thereby the further line of management can also be decided for a rational approach in the treatment of perimenopausal women with abnormal uterine bleeding.